2017
DOI: 10.1111/jav.01232
|View full text |Cite
|
Sign up to set email alerts
|

Effects of experimental night lighting on the daily timing of winter foraging in common European songbirds

Abstract: The ecological effects of light pollution are becoming better understood, especially in birds. Recent studies have shown that several bird species can use street lighting to extend activity into the night during the breeding season. However, most of these studies are correlational and little is known about the effects of artificial night lighting on the timing of activities outside the breeding season. During winter, low temperatures and short days may limit foraging opportunities and can negatively affect sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 64 publications
(129 reference statements)
1
19
1
Order By: Relevance
“…Indeed, light advanced activity onset of up to two hours in some individuals, and consequently increased nighttime activity by an average of one hour per night. This result is in line with previous studies that have shown that artificial light at night can increase nocturnal restlessness as well as foraging behaviour in great tits and other diurnal bird species (78)(79)(80). These effects are likely to come through the impact of light on physiological processes such as clock gene expression and melatonin production (56,58).…”
Section: The Effect Of Light On Activity Patternssupporting
confidence: 92%
“…Indeed, light advanced activity onset of up to two hours in some individuals, and consequently increased nighttime activity by an average of one hour per night. This result is in line with previous studies that have shown that artificial light at night can increase nocturnal restlessness as well as foraging behaviour in great tits and other diurnal bird species (78)(79)(80). These effects are likely to come through the impact of light on physiological processes such as clock gene expression and melatonin production (56,58).…”
Section: The Effect Of Light On Activity Patternssupporting
confidence: 92%
“…ALAN is therefore a novel challenge to biological systems that evolved over billions of years in the presence of only natural conditions of nocturnal illumination. ALAN is known to disrupt physiological processes that rely on the daily and seasonal rhythms of light cues, such as foraging behaviors [29][30][31][32], timing of emergence [33][34][35][36], reproduction [37][38][39][40], communication [41][42][43], and migration [38,44]. ALAN has been explored as one of the factors that can lead to the disruption and weakening of interdependent ecological systems and food webs.…”
Section: Ecologymentioning
confidence: 99%
“…For instance, ALAN disrupts circannual cycles, such as reproduction seasonality (Goldman 2001;Dominoni et al 2013;Robert et al 2015;Le Tallec et al 2016;Gaston et al 2017), which can lead to decreased reproductive success (Ikeno et al 2014;Cissé et al 2017 but see Stracey et al 2014 for increased reproductive success of birds). ALAN can also generate the appearance of a "night light niche" (Garber 1978;Russ et al 2015;Silva et al 2017), corresponding to the colonisation of the nocturnal niche by diurnal species and thus increasing interspecies competition and predation. Animals can also modify their foraging patterns in response to increased nocturnal visibility to reduce their risk of predation (reported in fishes: Clark and Levy 1988;Becker et al 2013, andin rodents: Clarke 1983;Kotler et al 1991;Bird et al 2004;Farnworth et al 2016).…”
Section: Introductionmentioning
confidence: 99%